Cities in the pre-modern Islamic world the urban impact of religion, state and society - Bennison, Amira K.; Gascoigne, Alison L. (SOAS/Routledge studies on the Middle East, 2007)
Aims to bring together research on aspects of urban life and structure by architectural and textual historians and archaeologists, engendering perspectives on urban life in the pre-modern Islamic world. This book examines case studies from seventh-century Syria to seventeenth-century Mughal India.